2021
DOI: 10.1159/000513234
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Sclerosis and Incidence of Urinary and Fecal Incontinence in Almost 9,000 Patients Followed Up for up to 10 Years in Germany

Abstract: Background: There is a lack of large studies on urinary (UI) and fecal incontinence (FI) following multiple sclerosis (MS) diagnosis. Thus, our goal was to investigate the association between MS and the incidence of UI and FI in patients followed up for up to 10 years in Germany. Methods: This study included patients who received an initial documentation of MS diagnosis in general practices in Germany during 2005–2018 (index date). Patients without MS were matched (1:1) to those with MS using propensity scores… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…The present retrospective cohort study was based on data from the Disease Analyzer (DA) database (IQVIA), which has already been used in several previous studies focusing on IBD or MS [ 10 12 ]. It contains anonymous data on diagnoses, prescriptions, as well as basic medical and demographic patient data derived from computer systems in office-based practices in Germany [ 13 ].…”
Section: Methodsmentioning
confidence: 99%
“…The present retrospective cohort study was based on data from the Disease Analyzer (DA) database (IQVIA), which has already been used in several previous studies focusing on IBD or MS [ 10 12 ]. It contains anonymous data on diagnoses, prescriptions, as well as basic medical and demographic patient data derived from computer systems in office-based practices in Germany [ 13 ].…”
Section: Methodsmentioning
confidence: 99%
“…It has previously been shown that the panel of practices included in the Disease Analyzer database is representative of general and specialized practices in Germany ( 9 ). Finally, this database has already been used in previous studies focusing on infectious mononucleosis ( 10 ) as well as MS ( 11 , 12 ).…”
Section: Methodsmentioning
confidence: 99%
“…These abnormalities cause chronic motor, sensory and autonomic dysfunction and lead to urinary symptoms such as urgency, frequency, and incontinence 3 . Previous studies have revealed that the incidence of urinary symptoms in pwMS ranges from 3.2% to 96% 4,5 . Five percent of pwMS present urinary symptoms as the first manifestation of the disease, and the incidence of these symptoms increase over time 4,6–8 .…”
Section: Introductionmentioning
confidence: 99%